2009
DOI: 10.1089/ten.tea.2009.0069
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Hyaluronic Acid to Alginate Embedded Chondrocytes Interferes with Insulin-like Growth Factor-1 SignalingIn VitroandIn Vivo

Abstract: The development of an engineered tissue requires a clear understanding of the interactions between the individual components. In this study, we investigated how the addition of hyaluronic acid (HA) to a cartilage tissue engineered scaffold alters chondrocytic expression, and specifically the expression of insulin-like growth factor-1 (IGF-1) signaling molecules. Bovine chondrocytes were embedded (7 million cells/mL) in 2.0% w/v alginate hydrogels containing varying HA concentrations (0, 0.05, 0.50, and 5.00 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 43 publications
(46 reference statements)
1
36
0
Order By: Relevance
“…80 Hyaluronan may stimulate chondrogenesis through interactions with cell surface receptors, 69,81 although conflicting results regarding the combination of hyaluronan with other types of hydrogels indicate a more complex system. 72 For example, the addition of hyaluronan to collagen I hydrogels increased markers of cartilage formation by encapsulated chondrocytes in a subcutaneous implantation model. 73 The addition of hyaluronan to cell culture medium increased deposition of type II collagen and glycosaminoglycans, markers of the cartilage phenotype, by chondrocytes encapsulated in alginate hydrogels, 82 but decreased such markers by chondrocytes encapsulated in collagen hydrogels.…”
Section: Type Of Polymermentioning
confidence: 99%
See 2 more Smart Citations
“…80 Hyaluronan may stimulate chondrogenesis through interactions with cell surface receptors, 69,81 although conflicting results regarding the combination of hyaluronan with other types of hydrogels indicate a more complex system. 72 For example, the addition of hyaluronan to collagen I hydrogels increased markers of cartilage formation by encapsulated chondrocytes in a subcutaneous implantation model. 73 The addition of hyaluronan to cell culture medium increased deposition of type II collagen and glycosaminoglycans, markers of the cartilage phenotype, by chondrocytes encapsulated in alginate hydrogels, 82 but decreased such markers by chondrocytes encapsulated in collagen hydrogels.…”
Section: Type Of Polymermentioning
confidence: 99%
“…83 Other studies have shown that the addition of hyaluronan to alginate hydrogels caused an increase in the expression of type I collagen, a marker of fibrous scar-like cartilage formation. 72 Interestingly, this trend was reversed in the presence of exogenous insulin-like growth factor-1 (IGF-1), suggesting a role for hyaluronan in the modulation of IGF-1 signaling by entrapped chondrocytes. 72 Chitosan: Chitosan is prepared by partial N-deacetylation of chitin, derived from the exoskeleton of arthropods, and is structurally similar to the glycosaminoglycans found in cartilage.…”
Section: Type Of Polymermentioning
confidence: 99%
See 1 more Smart Citation
“…It has been common practice that two or more biomaterials are combined to utilize the benefits of both. Matrix engineering by adding various components has been successful in producing composite materials, such as fibrin-alginate, 54 HAalginate, 55 and collagen-fibrin. 56 The results indicated the feasibility of the combined matrix gels as supports for cell proliferation without losing their chondrogenic potential.…”
Section: 44mentioning
confidence: 99%
“…37 HA is a nonsulfated GAG that constitutes a large proportion of cartilaginous ECM. Two or more polymers can be combined into gels to utilize the benefits of each component, such as fibrin-alginate, 48 HA-alginate, 49 and collagen-fibrin. 50 These previous studies demonstrated the capability of combined matrix gels to support cell proliferation without loss of chondrogenic potential.…”
mentioning
confidence: 99%